Nuclear magnetic resonance. - Oppenheimer, Norman J.; James, Thomas L. (Methods in enzymology, 1989)
This volume, as does Volume 176, provides a general background of modern NMR techniques, with a specific focus on NMR techniques that pertain to proteins and enzymology, and a "snapshot" of the current state-of-the-art in NMR experimental techniques. These books enable the reader to understand a given technique, to evaluate its strengths and limitations, to decide which is the best approach, and, finally, to design an experiment using the chosen technique to solve a problem.